The Development of a Concept Attainment Model Based E-Worksheet to Improve the Biology Conceptual Understanding of High School Students on the Material of Echinodermata Phylum Classification - Edelia, Dewi Fortuna; Kuswanti, Nur (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2025)
Understanding concepts is an important thing to be emphasized by students so that they are able to solve problems related to the material being studied. Understanding concepts is a prerequisite to train students' thinking skills. Indicators of understanding concept include, 1) interpreting, 2) classifying, 3) comparing, 4) exemplifying, 5) explaining, 6) inferring, and 7) summarizing. Concept attainment model-based e-worksheet can be one of alternative to train understanding concepts. The purpose of this research was producing concept attainment model-based e-worksheet on the material of the Echinodermata Phylum classification which is valid, practical, and effective to improve students' conceptual understanding. This research used the 4D model, contained steps of defining, designing, developing, and disseminating. The features included in the e-worksheet are "investigate the morphology", "observe the specimen", "define the concept", and "confirm the concept". Those present test items, material and visualization of Echinodermata as subjects that will be studied by students. The applicability of the e-worksheet was limited to 30 students of a senior high school in Surabaya. Data collection methods included validation, observation, tests, and response questionnaires. The e-worksheet was valid if it got validity score of ? 2.51, the e-worksheet was practical if its applicability of e-worksheet and positive response of students was ? 75%, and the e-worksheet was effective if it obtains n-gain score of ? 0.7. The research results showed an average of the validity score of 3.6 (very valid), the applicability reached 94% (very practical), the positive response from students reached of 98.4% (very practical), and the n-gain score reached 0.71 (very effective). Based on these data, the e-worksheet is declared valid, practical, and effective to improve students' understanding concepts.